Production Of Biofuel From Oil Palm Biomass Using Subcritical And Supercritical Liquefaction - Mazaheri, Hossein (2010)
This research project focused on the study of oil palm biomass decomposition to various liquid products in subcritical and supercritical solvents by using a high-pressure autoclave reactor with and without the presence of catalysts. The study which comprised of the decomposition process of oil palm biomass (Empty Fruit Bunch, Fruit Press Fiber, and Oil Palm Shell) in sub/supercritical solvents (water, methanol, ethanol, acetone and 1,4-dioxane) was investigated at the temperature range of 483 - 603K. The liquid products were separated into water soluble and bio-oil (as bio-crude) through extraction with water, benzene, diethyl ether, ethyl acetate, and acetone.